An Electrochemical Comparison of Single‐Walled and Multi‐Walled Carbon Nanotubes Utilizing Paeonol as the Model Drug. Issue 23 (19th June 2018) - Mane, Suyash; Chatterjee, Sanghamitra
Abstract: Herein, we report the development of a selective and highly sensitive electrochemical sensing of paeonol at carbon nanotubes modified glassy carbon electrode (GCE). Trace amount of paeonol was quantitated by employing square wave voltammetry technique for the first time based on the electrochemical oxidation of the analyte at the modified electrodes. The single walled carbon nanotubes (SWNTs) based sensor exhibited higher recognition ability of paeonol in comparison with the multi walled carbon nanotubes (MWNTs) based sensor. The linear dynamic range was found to be 100 nM – 25 μM for SWNTs modified GCE and 1–25 μM for MWNTs modified GCE. The sensitivity at SWNTs modified GCE was ∼ 3.5 times more than that at MWNTs modified GCE. The limit of detection was estimated to be 9.57 nM and 0.63 μM corresponding to SWNTs and MWNTs modified GCE respectively. The influence of experimental parameters affecting sensor response was optimized. The stability, reproducibility tests and interference effects were demonstrated to confirm the reliability of the proposed sensor. The applicability of the developed sensor was successfully assessed through convenient measurements of paeonol in biological samples and Cortex moutan which exhibits anticancer effect. Abstract : Comparison of the electrocatalytic activity of single walled and multi walled carbon nanotubes modified GCE for paeonol quantitation. The augmented electroactive surface area of single walled carbon nanotubes modified GCE engendered to the low detection limit with a high sensitivity. Selective determination of the drug in Cortex moutan and real samples of healthy human was effectuated. The developed sensor for paeonol has potential clinical and biomedical applications.